Coping in times of disruption and deprivation-Experiences of family members during COVID‐19 patients' critical illness: A qualitative study - Helene Berntzen; Ranveig Lind; Hanne Alfheim; Kirsti Tøien (Wiley, 2023)
Abstract Aim To explore the experiences and needs of family members during the course of COVID‐19 critical illness from onset to rehabilitation. Design An exploratory qualitative study. Methods Twelve family members of surviving critically ill COVID‐19 patients and restricted from visiting the patients, were interviewed digitally. Reflexive thematic analysis was used. Results Three themes were generated from the data; 'Experiencing a double burden', 'Becoming an insignificant other' and 'Regaining significance'. Family members were often ill themselves, which represented an extra burden when the patient deteriorated. From admission, the family members became bystanders, deprived of most contact with the patients, as communication and information from the intensive care unit appeared unstructured and haphazard. However, when patients were discharged, great responsibility was placed on the family members.